The role of wound macrophage anti-inflammatory polarization and MANF production in the treatment of diabetic foot with tibial cortex transverse transport - MO Ruiqing; YANG Shenghui; SU Hongjie; HUA Qikai (Guangxi Yike Daxue xuebao)
Objective To investigate the correlation between midbrain astrocyte-derived neurotrophic factor (MANF) levels in peripheral blood and local wound of diabetic foot patients and the anti-inflammatory polarization of macrophages induced by tibial cortex transverse transport (TTT), with a preliminary exploration of the molecular mechanisms by which TTT alleviates inflammation in diabetic foot ulcers. Methods Ten diabetic foot ulcer patients who underwent TTT at the First Affiliated Hospital of Guangxi Medical University from July 2023 to December 2023 were enrolled in this study as subjects, and were divided into preoperative and postoperative groups as self-control. Peripheral blood samples were collected before treatment and one month after treatment for MANF protein enzyme-linked immunosorbent assay (ELISA); tissue samples from the wound margins were taken for the hematoxylin-eosin (H&E) staining to observe histological changes; Masson's trichrome staining was used to observe changes in collagen fiber deposition in the wound tissue; immunofluorescent staining for mannose receptor (CD206), inducible nitric oxide synthase (iNOS), and MANF was performed on wound tissue to observe the expression and distribution of these proteins. Results The average healing time for chronic ulcers in 10 diabetic foot patients was (4.0±0.8) months. The healing process gradually transitioned from the inflammatory phase to the proliferative repair phase. Postoperatively, bright red granulation tissue began to appear and gradually filled the tissue defects after debridement. Epithelial tissue from the margins migrated and proliferated towards the center, eventually leading to complete repair of the tissue defects after debridement of diabetic foot ulcers, leaving only linear scars. An increase in serum MANF protein levels was detected compared to preoperative levels (P < 0.05). Histological observations indicated that the wound exhibited characteristics of the proliferative repair and collagen remodeling phase, with a gradual resolution of inflammation and a decrease in inflammatory cell infiltration. Postoperatively, a rich microvascular structure and glands were observed, with well-organized skin tissue structure, increased collagen deposition (P < 0.05), a significant decrease in the ratio of iNOS positive cells to CD206 positive cells (P < 0.05), and a significant increase in the density of MANF positive cells per unit area compared with pre-operation (P < 0.05). Conclusion The TTT technique promotes wound healing by increasing the levels of MANF protein in the serum and wound tissue of diabetic patients and facilitating the transition of macrophages in the wound area towards the M2 phenotype.